Housing for young people: what are their opportunities? / Mahazril ‘Aini Yaacob, Siti Hajar Abu Bakar and Wan Nor Azriyati Wan Abdul Aziz - Yaacob, Mahazril ‘Aini; Abu Bakar, Siti Hajar; Wan Abdul Aziz, Wan Nor Azriyati (Penerbit UiTM (UiTM Press), 2017)
Housing does not only serve the basic needs of the citizens, but it is also considered as one of the important features of independent living. A comprehensive literature search revealed that access to housing is vital in the transition to adulthood, mainly to ensure that young adults enjoy a higher quality of life. Young adults face many hardships in their pursuit of adequate and affordable housing. Nevertheless, the act of leaving home, are typically determined by the economic resources (income) and other influential factors. The debate on establishing the homeownership was rampantly discussed by numerous researchers. However, efforts to examine the factors influencing the housing opportunities among the young people are limited. In response to this need, a preliminary study was carried out to identify the factors affecting the housing opportunities among the young people. Except for locational factor, affordability, housing knowledge and structural factors play prominent roles in inducing housing opportunities among the youth. Therefore, strategies such as comprehensive information about housing schemes should be made available and accessible to the young people. Additionally, other relevant parties, such as financial institutions and developers, may need to revise their requirement for loan financing, and the eligibility criteria. Overall, these measures should be able to ensure that young can people enjoy housing opportunities and improve their quality of life